Genetic Variance for Autism Screening Items in an Unselected Sample of Toddler-Age Twins - Stilp, Rebecca L. H. (2010)
OBJECTIVE: Twin and family studies of autistic traits and of cases diagnosed with autism suggest high heritability; however, the heritability of autistic traits in toddlers has not been investigated. Therefore, this study’s goals were to (1) screen a statewide twin population using items similar to the six critical social and communication items widely used for autism screening in toddlers (Modified Checklist for Autism in Toddlers); (2) assess the endorsement rates of these items in a general population; and (3) determine their heritability. METHOD: Participants composed a statewide, unselected twin population. Screening items were administered to mothers of 1,211 pairs of twins between 2 and 3 years of age. Twin similarity was calculated via concordance rates and tetrachoric and intraclass correlations, and the contribution of genetic and environmental factors was estimated with single-threshold ordinal models. RESULTS: The population-based twin sample generated endorsement rates on the analogs of the six critical items similar to those reported by the scale’s authors, which they used to determine an autism threshold. Current twin similarity and model-fitting analyses also used this threshold. Casewise concordance rates for MZ (43%) and DZ (20%) twins suggested moderate heritability of these early autism indicators in the general population. Variance component estimates from model-fitting also suggested moderate heritability of categorical scores. CONCLUSIONS: Autism screener scores are moderately heritable in 2–3 year-old twin children from a population-based twin panel. Inferences about sex differences are limited by the scarcity of females who scored above the threshold on the toddler-age screener.